2013
DOI: 10.1002/jgrc.20217
|View full text |Cite
|
Sign up to set email alerts
|

Rates and mechanisms of turbulent dissipation and mixing in the Southern Ocean: Results from the Diapycnal and Isopycnal Mixing Experiment in the Southern Ocean (DIMES)

Abstract: [1] The spatial distribution of turbulent dissipation rates and internal wavefield characteristics is analyzed across two contrasting regimes of the Antarctic Circumpolar Current (ACC), using microstructure and finestructure data collected as part of the Diapycnal and Isopycnal Mixing Experiment in the Southern Ocean (DIMES). Mid-depth turbulent dissipation rates are found to increase from O 1 Â 10in the Scotia Sea, typically reaching 3 Â 10 À9 W kg À1 within a kilometer of the seabed. Enhanced levels of turbu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
221
5
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(257 citation statements)
references
References 40 publications
(51 reference statements)
29
221
5
1
Order By: Relevance
“…The presence of a near-bottom finescale overprediction signal in the strain-only estimates in particular suggests that contamination by LADCP instrument noise, an issue that tends to lead to an overestimation of the shearinferred dissipation rates in regions of weak stratification (Kunze et al 2006), does not explain the bulk of the signal. This is consistent with Sheen et al (2013), who also document a near-bottom overprediction signal in strainonly estimates. It is nonetheless prudent to consider the dependence of the finescale overprediction observed on metrics of instrumental noise and the vertical wavelength integration limits in detail.…”
Section: A Near-bottom Finescale Parameterization Overprediction Andsupporting
confidence: 90%
See 2 more Smart Citations
“…The presence of a near-bottom finescale overprediction signal in the strain-only estimates in particular suggests that contamination by LADCP instrument noise, an issue that tends to lead to an overestimation of the shearinferred dissipation rates in regions of weak stratification (Kunze et al 2006), does not explain the bulk of the signal. This is consistent with Sheen et al (2013), who also document a near-bottom overprediction signal in strainonly estimates. It is nonetheless prudent to consider the dependence of the finescale overprediction observed on metrics of instrumental noise and the vertical wavelength integration limits in detail.…”
Section: A Near-bottom Finescale Parameterization Overprediction Andsupporting
confidence: 90%
“…Sheen et al (2013) similarly argue against an influence of integration limits on the finescale overprediction signal seen in DIMES data. In that study, the High Resolution Profiler 2 (HRP2) measured current velocities that FIG.…”
Section: ) Relation To Vertical Scales Consideredmentioning
confidence: 98%
See 1 more Smart Citation
“…For the case where the planetary vorticity gradient is nonzero, we use β = 2 × 10 −11 m −1 s −1 which corresponds to a non dimensional β (which measures the relative importance of the planetary vorticity gradient relative to the mean shear) of β * = β b/Λ ∼ = 0.47. In midlatitudes, a typical ocean jet has U ∼ 0.5 m s −1 at the surface (e.g., Sheen et al 2013), whereas the barotropic jet used here has a value more typical of the a depth-mean over the main thermocline.…”
Section: Numerical Model Descriptionmentioning
confidence: 99%
“…A high-resolution model clearly showed that the link between surface-intensified eddying geostrophic flows, bottom-enhanced velocities, topographic internal gravity waves, and energy dissipation is of primary importance for the energetic of the Antarctic Circumpolar Current (Nikurashin et al 2013). Observations of turbulent mixing also support this scenario in the Southern Ocean (Heywood et al 2002;Naveira Garabato et al 2004;Sloyan 2005;Sheen et al 2013).…”
mentioning
confidence: 96%